Downward social comparison positively promotes altruism: the multi-mediating roles of belief in a just world and general life satisfaction - Hu, Yunjun; Cui, Guanyu; Jiang, Linxi; Lan, Xiaoyu (Frontiers in Psychology, 2024)
Introduction This study examined the underlying mechanism of the relationship between downward social comparison (DSC) and altruism through two conceptually important but rarely studied factors: belief in a just world (BJW) and general life satisfaction (GLS). Methods The study utilized a two-time-point design, spaced 2 months apart, with a sample of 1,764 college students from China. The study measured DSC, altruism, BJW, and GLS. Results The findings revealed a significant positive predictive effect of DSC on college students’ altruism and belief in a just world (BJW). Notably, GLS emerged as a multi-mediating factor in this relationship. The study also revealed that both subscales of BJW, namely personal belief in a just world (PBJW) and general belief in a just world (GBJW), played distinct roles in the mediation model. PBJW exhibited a stronger mediating effect, suggesting that DSC can foster individual altruism and BJW. Particularly, BJW was identified as enhancing GLS, subsequently promoting altruistic behavior. Conclusion This study contributes to the existing literature on social comparison by shedding light on the relationship between DSC, altruism, and the mediating role of belief in a just world and GLS. The findings underscore the potential for promoting altruistic behavior among college students through interventions targeting beliefs in a just world, especially at the personal level, and enhancing GLS.